Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 166020764 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is one of (Unknown evidence, Living Specimen, Fossil, Specimen, Material sample)", { "or" : [ "IdentifiedBy is not null", "RecordedBy is not null" ] }, { "or" : [ { "not" : { "VerbatimScientificName" : [ "is not null" ] } }, { "not" : { "or" : [ "VerbatimScientificName ~*BOLD:*", "VerbatimScientificName ~*BOLD-*", "VerbatimScientificName ~*BIOUG*" ] } } ] } ] } The dataset includes 166020764 records from 21127 constituent datasets: 14 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 2 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 73 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 10 records from Analyses of the recent components of sediment core PS1277-1. 237 records from Nannofossil abundance of Hole 60-458. 11961 records from MEXU/Leguminosae. 44 records from An overlooked diversity-the Costellariidae (Gastropoda: Neogastropoda) of the Miocene Paratethys Sea. 15 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 10 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 2 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 899 records from Planktic foraminifera counts of sediment core RC08-49. 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 1 records from A new name for Dendronephthya kukenthali Gravier, 1908 (Octocorallia, Nephtheidae): Dendronephthya perezi nom. n.. 14 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 8 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 6 records from A review of the Glossogobius giuris complex in Australia, with wider discussion on nomenclature and possible synonymies. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 5 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 44 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 50 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 9 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 209 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 20 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 55 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 382 records from orthopteracollections-nhmj-ioj. 83 records from Invasive alien species Impatiens glandulifera Royle in the Republic of Karelia. 2 records from Carnivores of Syria. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 6 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 159 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 48 records from Muséum d'Avignon. 619 records from Mycology collection, Norwegian Forest and Landscape Institute. 184 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 208 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 14 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 5 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2614 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 4 records from Dinoflagellate abundance of Hole 14-144. 20 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 49 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 25 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 302630 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 6 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 126 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 172 records from UWIZM Anoles. 8 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 399 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 2 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 525 records from Herbarium of the Institute of the problems of Northern development (TMN). 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 6 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 7 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 1107 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 73 records from Faunal assemblage of sediment core TR149-31. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 9 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 134 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 21716 records from Herbier Louis-Marie (QFA) - Collection de lichens. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 73 records from Planktic foraminifera abundance of Hole 49-409. 171 records from Planktic foraminifera abundance of Hole 29-284A. 2 records from New species of Isometopinae (Hemiptera: Miridae) from the Ivory Coast and Yemen. 592882 records from Plant. 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 38 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 122 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 15 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 116 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 14 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 12784 records from Colecção Entomológica IIA. 16791 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 1 records from A new genus of Bambusicolaceae (Pleosporales) on Corylus avellana (Fagales) from Italy. 1 records from A new species of Microdaccus SCHAUM 1864 from Cyprus (Coleoptera, Carabidae, Lebiini). 43 records from Nannofossil abundance of Hole 10-91. 7148 records from DMNS Egg Collection (Arctos). 1092 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 97 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 29 records from Four new species of the subgenus Tachycines (Gymnaeta) (Rhaphidophoridae Aemodogryllinae: Aemodogryllini) from caves in northern Guizhou, China. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 1700 records from BioGIS - Bryophytes - HUJ collections. 1 records from Contribution to the knowledge of oribatid mites of the genus Austrocarabodes (Acari, Oribatida, Carabodidae) of Madagascar. 15 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 2 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 54907 records from Herbarium Universitatis Daugavpiliensis. 1 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 1393 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 1 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 12 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 335 records from Dinoflagellate cyst counts on sediment core ABC26. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1 records from Megaluropidae *. 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 19740 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 5 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 6207 records from Plecoptera. 49 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 8 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 10 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 10 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 1 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 166 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 69 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 16 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 31 records from NZCS Brownsberg Nature Park Monitoring. 985 records from Bees in the UVM Zadock Thompson Zoological Collection. 99 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 24 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 13 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 222 records from Neogene palynomorpha from site 81-552. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 1 records from Discovery of the bee genus Perdita in the West Indies (Hymenoptera: Andrenidae): a new species from Isla Cabritos in the Dominican Republic. 124216 records from The Himalayan Uplands Plant database (HUP Version 1). 6651 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 12006 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 2 records from Miliusa gokhalaei, a new species of Annonaceae from India with notes on interrelationships, population structure and conservation status. 27 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 102 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 109 records from Collections ichtyologiques et herpétologiques (BOUM). 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 7900 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 10 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 6 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 19 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 2457 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 878 records from COA Bird Collection (Arctos). 34 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 2 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 1 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 32040 records from University of Guam Insect Collection. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 6 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 298 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 1 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 570 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 2493 records from Museu de Ciències Naturals de Barcelona: BGJBB. 21 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 102 records from Nannofossil abundance of Hole 24-232. 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2516 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 916 records from UWIZM Molluscs. 5279 records from MCP-Aves - Coleção de Aves. 135 records from Nannofossil abundance of Hole 36-329. 5 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 336 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 45 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 1 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 10 records from Changes in the genus Beana Walker (Beaninae Zahiri & Holloway) with two new species and removing Beana nitida Tams to a new genus Beanoides (gen. nov.). 996 records from Pollen profile ADR353. 270 records from bmhs_weatherheadshell_collection. 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 755 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 2 records from A new species of Eupatorus Burmeister, 1847 related to Eupatorus birmanicus Arrow, 1908 from southwestern China (Coleoptera: Scarabaeidae: Dynastinae). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 10 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 254307 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 5 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 74 records from Living Cirripedia. 9 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 10 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 6 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (PLECHA). 7 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 5 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 12027 records from University of Nebraska State Museum Birds Collection. 28579 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 116 records from Dinoflagellate cysts of ODP Hole 189-1172D. 2 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 407 records from Planktic foraminifera abundance of Hole 45-395. 75334 records from Entomology Collection at the Natural History Museum of Utah. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 7 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 8 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 142 records from Hartland Nature Club Lepidoptera Collection. 120307 records from ALCB - Herbário Alexandre Leal Costa. 3 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 3183 records from Herbarium specimens of Limoges university (LIMO). 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 12 records from Type specimens of Ichneumonidae (Hymenoptera) described by Brèthes held in the Museo Argentino de Ciencias Naturales “ Bernardino Rivadavia ”, Argentina. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 13662 records from UTEP Invertebrates (Arctos). 167 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4180 records from Diptera Collection of Museum and Institute of Zoology PAS. 15 records from Fish occurrence in Kuban River basin. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 9 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 2 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 1321 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 13 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 2 records from Planktic foraminifera abundance of Hole 19-191A. 23643 records from CNIN/Abejas de México/Apoidea. 1 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 915 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 6 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 707 records from Flora útil del Municipio de la Huerta, Jalisco. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 1719 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 23 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 26 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 1 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 18 records from Revision of the spider genus Ischnocolus Ausserer, 1871 (Mygalomorphae: Theraphosidae: Ischnocolinae). 15 records from Nannofossil abundance of Hole 10-93. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 12 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 245 records from Planktic foraminifera counts of sediment core V14-77. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 144 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 19 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 248870 records from hymenoptera. 89666 records from Naturalis Biodiversity Center (NL) - Crustacea. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 11067 records from Danish Ants (Formicidae). 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 25 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 404 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4481 records from Iowa State University Fishes Collection. 4 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 300 records from EDIT - ATBI in Gemer area (Slovakia). 553 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 49 records from Nannofossil abundance of Hole 27-259. 52 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 77 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 3 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 232 records from Planktic foraminifera abundance of Hole 21-207. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 3 records from Cyana barbora, a new species from Sichuan, southwestern China (Lepidoptera Erebidae, Arctiinae, Lithosiini). 23 records from Benthic foraminifera abundance of Hole 93-603. 11648 records from WOLL AVH data. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 1450 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 2 records from Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China. 84 records from Ostracoda abundance of Hole 48-403. 48 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3638 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 8 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 219 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 2 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 58618 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 192 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 7 records from Evolution Of Large Carnivores During The Mid-Cenozoic Of North America: The Temnocyonine Radiation (Mammalia, Amphicyonidae). 10000 records from 2020_biodiversity_information_specimen. 1697 records from ISM Ichthyology Collection. 144 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 3 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 19 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 1549 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 27 records from Nannofossil abundance of Hole 9-79. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 20810 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 37 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 100 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 4546 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1 records from Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 568 records from Planktic foraminifera counts of sediment core V27-178. 314 records from Foraminifera abundance of Hole 64-481. 2 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 1862 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 4 records from Replacement names and nomenclatural comments for problematic species-group names in Europe's Neogene freshwater Gastropoda. 280 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 15700 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 1 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 5 records from Two new species of Lagenandra (Araceae) from the Wet Zone of Sri Lanka. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2197 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 2011 records from Fish (NHMK-PI). 5 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 27 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 37 records from Species of the bee genus Centris Fabricius, 1804 described by Heinrich Friese (Hymenoptera: Apidae). 18 records from A morphological, phylogenetic and phylogeographic reappraisal of the land crabs Gecarcinus quadratus De Saussure, 1853, and G. lateralis Fréminville in Guérin 1832 (Decapoda: Gecarcinidae). Are they different species?. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 6 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 820 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 211 records from Planktic foraminifera abundance of Hole 14-142. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 37 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 52 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 59 records from Nannofossil abundance of Hole 73-521A. 7438 records from BioGIS - Vascular plants - Israeli Gene Bank. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 5 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 24 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 7061 records from University of Cincinnati, Margaret H. Fulford Herbarium. 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 85 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 16 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 8863 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 4 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 488 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 91 records from Vascular plants occurrences in Dokdo Islands, Korea, based on the herbarium collections and legacy botanical literature. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 19 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 62 records from Foraminifera abundance of Hole 33-317A. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 51 records from Colección de Aráceas del Jardín Botánico San Jorge. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 31 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 6 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 1 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 40 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 22 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 98 records from Nannofossil abundance of Hole 67-499B. 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 463 records from Foraminifera abundance of sediment core IN68-9. 423 records from Colección de Bacterias del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 1 records from Timea bioxyasterina sp. n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida). 3 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 7872 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 11 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 6 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 6 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 11984 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 54 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 34 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 2 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 3 records from Zoology in the Middle East. 13 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 53 records from Nannofossil abundance of Hole 1-3. 1 records from Three new species of the family Scathophagidae (Diptera) from the Palaearctic region with a redescription of the male of Amaurosoma longicorne. 202 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 71 records from Nannofossil abundance of Hole 6-55. 3 records from Four new species records of Antennoseius and Anystipalpus (Acari: Mesostigmata: Ascidae) phoretic on Carabidae beetles from France. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 99 records from Planktic foraminifera abundance of Hole 27-262. 42 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 137604 records from Arizona State University Hasbrouck Insect Collection. 27 records from Planktic foraminifera abundance of Hole 27-260. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 3363 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 38 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 156 records from Chironomid remains in the sediment sequence of Site PG1212. 5278 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 2277 records from Lista florística de la Costa Grande del estado de Guerrero. 10 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 351 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 184 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 16 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 24380 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 194 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 8260 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 3959 records from The Broward College Insect Collection. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 8 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 13 records from Eubria mesoamericana Barr and Shepard (Coleoptera: Psephenidae: Eubriinae), a New Psephenid Species from Central America with an Enigmatic Generic Distribution. 6 records from Planktic foraminifera abundance of Hole 53-418B. 8 records from Discovery of Lymantini weevils (Coleoptera: Curculionidae: Molytinae) outside the Americas: Devernodes, a new genus for five new species from Southeast Asia. 2071 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 1191 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 10 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 3 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 16 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 76523 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 4 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 11 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 3 records from First record of the genus Microtityus Kjellesvig-Waering, 1966, from Puerto Rico, with description of two new species (Scorpiones: Buthidae). 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 5565 records from Weber State University Herbarium. 26 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 923 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 3 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 138 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 4 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 351 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 136 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 79 records from Diatom abundance of Hole 95-613. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 72 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2 records from Results of palynological analysis of Hole 302-M0004C. 3 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 17 records from Diura Washingtoniana (Hanson) Resurrected From Synonymy With D. Nanseni (Kempny) (Plecoptera: Perlodidae), Supplemented With A Description Of The Larva And Egg And Comparison To Other Congeners. 5 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 1955 records from SIM-Fungal records compiled by Joan Montón. 614726 records from Western Australian Museum provider for OZCAM. 5 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 3940 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 448 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 709 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 23 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 91370 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 4 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1513 records from M. Gollop Collection. 45829 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 12 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 2 records from Taxonomic notes on the genus Hydrobaenus with description of H. simferopolus sp. nov. from Crimea (Diptera: Chironomidae). 7 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 453 records from Benthic foraminifera counts of sediment core PS1852-2. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 234 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 18 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 110 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 75 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 158 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 16 records from Insect Collections of Okomu National Park- Nigeria. 231144 records from University of Minnesota Insect Collection. 15 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1 records from Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucatán Peninsula. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 1581 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 2012 records from Pollen profile RAC20, Lake Racou, France. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 1 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 4 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10898 records from Inventario de Hymenóptera; parasítica en México. 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 46 records from Planktic foraminifera abundance of Hole 9-76. 3139 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 11 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 38 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 30 records from Nannofossil abundance of Hole 24-233A. 2767 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 3507 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 312 records from Lucanidae. 80 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 100361 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 5 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 4 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 475 records from Planktic foraminifera counts of sediment core A15-558. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 25817 records from MSUM Ichthyology and Herpetology Collections. 70 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 10 records from Benthic macrofauna abundance of sediment core 13200-008. 406 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 6 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 4 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 12 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 7600 records from ERBG AVH data. 5 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 18 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 164752 records from Tiroler Landesmuseum Ferdinandeum. 5 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 65 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 4 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 59 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1227 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 78 records from Mammals (GNHM-MM). 6 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 25 records from Planktic foraminifera abundance of Hole 51-417B. 8 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 372 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 4 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 2 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 3754 records from California State University, Long Beach Birds. 22 records from Ostracoda abundance of Hole 24-238. 18 records from Thirteen new records of ferns from Brazil. 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 6 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 2 records from Astragalus orientopersicus, sp. nov. (Fabaceae), a new taxon from the Khorassan province (Iran). 2 records from Description of a new species of the genus Maua Distant (Hemiptera, Cicadidae) from China. 178047 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 7 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 20 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 273 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 1 records from A new species of the genus Nenasa (Hemiptera: Fulgoroidea: Caliscelidae) from mainland China. 27 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 13 records from Ameroculodes miltoni, a new species of estuarine amphipod (Crustacea: Malacostraca: Peracarida: Oedicerotidae) from the southeastern United States. 26 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 32 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 5 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 697 records from 2019_NSMK_PL. 321 records from Foraminifera abundance of Hole 74-526A. 184 records from Dinoflagellate abundance of Hole 81-555. 10 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 68 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 983 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1872 records from Herbier National de Guinée (HNG). 21 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 3 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 83 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 66116 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 73 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 8 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 4 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 79 records from Nannofossil abundance of Hole 31-299. 56 records from Catalogue of the Syrphidae of Egypt (Diptera). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 21 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 125 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 9 records from Morphological systematics of kingsnakes, Lampropeltis getula complex (Serpentes: Colubridae), in the eastern United States. 1 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 9 records from Nannofossil abundance of Hole 2-11. 6131 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 160 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 100 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 42 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 1870 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 15 records from Nannofossil abundance of Hole 6-48B. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 214 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 29876 records from European Moth Nights. 65 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 964 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 26 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 79 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 5 records from A northern range extension of a Canadian species of Special Concern, Dielis pilipes (Hymenoptera: Scoliidae), in the Okanagan Valley of British Columbia. 16 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 8 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 2 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 5 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 15 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 4 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 39 records from Planktic foraminifera abundance of Hole 14-137. 2626 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 45 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 195148 records from inatura - Erlebnis Naturschau Dornbirn. 12 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 168 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 1180 records from Birds (NHMK-BI). 1 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 4 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5780 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 36 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 2 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 102245 records from Database of invertebrates collected in Mongolia. 917 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 3 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 38 records from Nannofossil abundance of Hole 10-89. 10075 records from Nematoda of Costa Rica (INBio). 1 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 136 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 14 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 3 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 605 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 190 records from Pollen record of profile 3TZ. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 336156 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 11 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 79 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 17 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 98 records from Brock University Herbarium (BU). 148 records from Herbarium BSG Hepaticopsida. 117 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 19 records from Taxonomic revision of the genus Oplognathus MacLeay, 1819 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini). 19 records from A New Mormoopid Bat From The Oligocene (Whitneyan And Early Arikareean) Of Florida, And Phylogenetic Relationships Of The Major Clades Of Mormoopidae (Mammalia: Chiroptera). 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 118 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 70 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 48 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 3 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 6 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 2 records from Onthophagus fragosus n. sp. a second endemic species of Onthophagus Latreille from Cuba (Coleoptera: Scarabaeidae, Scarabaeinae). 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 118 records from Pollen record of profile 3TZ2. 2 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Reptiles y anfibios). 13 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 7798 records from MHA Herbarium: Collections of mosses from Yana-Indigirka Region, Yakutia, Russia. 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 37 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 1640 records from La familia Asclepiadaceae en México. 17 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 5 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 29 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 51 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 180 records from Benthic foraminifera abundance of Hole 41-366A. 1 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 1 records from Redescription of Favognathus insularis (Luxton) (Acari: Trombidiformes: Cryptognathidae) from Brazil, with a key to the world species of Favognathus. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 552 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 62798 records from MLZ Bird Collection (Arctos). 9 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 32 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 15 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 1 records from A new species of cave inhabiting Scotoleon Banks from Baja California (Neuroptera: Myrmeleontidae: Brachynemurini). 412 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 5 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 10 records from Culicidae of Guam. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 7 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 178 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 4 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 126 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 4240 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 25 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 176 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 1 records from Developmental Biology among Corbiculate Bees: Bombus impatiens, Including Observations on Its Egg Eclosion. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 94 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1368 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 2 records from Volutellonectria (Ascomycota, Fungi), a new genus with Volutella anamorphs. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 17 records from Analyses of the recent components of sediment core PS1011-1. 271712 records from Allan Herbarium (CHR). 184735 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 56 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 14232 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 22 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 17 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 1 records from MVZ Herp Observations (Arctos). 306 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 2 records from A new species of Aegidium Arrow (Coleoptera: Scarabaeidae: Orphninae) from Colombia. 145 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 6 records from Foraminifera abundance of Hole 58-442. 4 records from New Species Of Tyloperla (Plecoptera: Perlidae) From Vietnam And Thailand. 2 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 13 records from Coleção de Coleoptera da Universidade de Brasília. 766 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 5 records from TWO NEW SPECIES OF ORIPODOIDEA (ACARI: ORIBATIDA) FROM VIETNAM Sergey G. E and Alexander E. A. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 15 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 53 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 28537 records from Marie-Victorin Herbarium (MT) - Bryophytes. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 417 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 58 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 109 records from Dinoflagellate cysts from sediment core PS1295-4. 5 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 18 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 183 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 3212 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 830 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 655 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 9 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 1 records from Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (4) Hylaeus sinensis sp. n. - Nachweis der montan-disjunkten Verbreitung einer Artengruppe um Hylaeus niger B (Apidae, Colletinae). 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 255394 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 73980 records from Naturalis Biodiversity Center (NL) - Pisces. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 448 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 387 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 18 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 495 records from Radiolaria assemblage in sediment core GIK23414-6. 308 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 36 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 27 records from Planktic foraminifera abundance of Hole 84-566C. 43 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 13 records from The Endemic Sulawesi Fish Genus Lagusia (Teleostei: Terapontidae). 8 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 18 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 3 records from The Evaniidae (Hymenoptera: Evanioidea) of Turkey. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 18 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 32 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 20 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 2128 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 9 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 23 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 21 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 1 records from First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa). 2 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 796 records from Microfossil abundance of Hole 16-158. 7 records from Rajburicoris, a new genus of Cardiastethini, and discussion of the systematic position of Dufouriellus (Hemiptera: Heteroptera: Anthocoridae). 14 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 342 records from Nannofossil abundance of Hole 78-543. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 2 records from Glasgow Museums BRC: Chrysomelidae. 1 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 17 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 44 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 70 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 4400 records from USAC Mammals Collection. 361 records from Nannofossil abundance of Hole 66-490. 2 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 16 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 25 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 6 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 79 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 22 records from PSUZC-Reptile Collection. 2 records from A new water mite species of the Hygrobates fluviatilis-complex from Russia (Acari Hydrachnidia, Hygrobatidae). 820 records from Nannofossil abundance of Hole 82-558A. 33 records from Planktic foraminifera counts of sediment core RC13-154. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 37 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 41 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 13 records from Diatom abundance of Hole 60-460. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 16 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 6 records from A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India with the reassignment of Potamiscus pealianus (Wood-mason, 1871). 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 5 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 3 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 289 records from Planktic foraminifera abundance of Hole 42-372. 69 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 49145 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3435 records from MEXU/Flora de Oaxaca. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 3 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 83 records from Heavy minerals of sediment core PL94-64. 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1914 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 6 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 52 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 15 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 105985 records from Herps Specimens. 7 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 37158 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 183 records from (Table 6) Ostracod assemblages of sediment core 9409. 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 15 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 3 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 6 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 3 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3571 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 384 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 271 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 63020 records from EAC - Herbário Prisco Bezerra. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 2 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 2 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1564 records from Leif Richardson Vermont Bee Specimens. 239 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 153 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 6 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1153 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 26 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 27 records from A contribution to the earthworm diversity (Clitellata, Moniligastridae) of Kerala, a component of the Western Ghats biodiversity hotspot, India, using integrated taxonomy. 14 records from Nannofossil abundance of Hole 25-249. 4 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 31 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 5 records from A Middle Devonian Trilobite Assemblage from Venezuela. 44 records from Three new species and six new records of Scathophagidae (Diptera) from Japan with a key to the Japanese genera. 7 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 271973 records from ARABEL - Arachnologia Belgica. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 12 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 2984 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 66 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 22 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 4 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 60 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 45 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 158 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 43 records from UWIZM Cnidarians. 1 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 108 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 2 records from Integrative taxonomy at the nexus of population divergence and speciation in insular speckled rattlesnakes. 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 15484 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 185630 records from Tasmanian Museum and Art Gallery provider for OZCAM. 962 records from TTRS Mammals. 1 records from Pindamoraria boraceiae, a new genus and species of freshwater Canthocamptidae (Copepoda, Harpacticoida) from Brazil. 6 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 20 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 9 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 25 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 2 records from Benthic foraminifera abundance of Hole 42-376. 37 records from Brown bear monitoring data from Deosai National Park. 1298 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 231 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 624 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 3627 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 82 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 24 records from A new species of Thamnodynastes Wagler, 1830 from western Amazonia, with notes on morphology for members of the Thamnodynastes pallidus group (Serpentes Dipsadidae, Tachymenini). 99567 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2580 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 30 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 2765 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 44 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 89 records from Faunal assemblage of sediment core TR149-32. 516 records from Nannofossil abundance of Hole 15-149. 1386 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2310 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 24 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 5 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 16 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 9 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 171 records from Foraminifera abundance of Hole 57-440A. 41 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 11 records from The genus Arrhopalites (Collembola, Arrhopalitidae) in Asia, with the description of two new Japanese species of Yosiis collection. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 8 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 56 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 264 records from What bug is that. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 4 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 109 records from Planktic foraminifera abundance of Hole 18-181. 7 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 45 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 1 records from A dryinid wasp in Early Eocene amber from the Paris basin (Hymenoptera: Dryinidae). 23226 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1787 records from Colección del Herbario de la Universidad de los Llanos. 23 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 959 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 10 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 2 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 44 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 2 records from Pygmodispus (Pygmodispus) paraequestris spec. nov. (Acari: Heterostigmata: Scutacaridae) from Turkmenistan. 14 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 59 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 4 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 2 records from A new species of Hemilea Loew and two new records of Trypetini (Diptera Tephritidae: Trypetinae) from India. 2 records from Microfossil abundance of Hole 21-208. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 6859 records from Plan de vertebrados de la Patagonia. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 13 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 61 records from Planktic foraminifera distribution of sediment core TRI171-27. 2954 records from Distribution of planktic foraminifera of sediment core M35003-4. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 105 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 141 records from Herbario del Museo de Historia Natural C.J. Marinkelle. 16 records from Discovered online: Hibiscus hareyae sp. nov. of sect. Lilibiscus (Malvaceae), threatened in coastal thicket at Lindi, Tanzania. 12 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 78 records from Invasive alien species Noccaea caerulescens (J. Presl & C. Presl) F. K. Mey. in the Republic of Karelia. 4 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 13 records from Planktic foraminifera abundance of Hole 19-185. 84 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 19011 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 12 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 192 records from (Table IIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of the Ben Gurion Section, Israel. 11 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crustáceos). 638 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 29 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 5 records from A Catalogue and Historical Study of the Odonata of Ecuador. 2705 records from Biodiversity of the Desna river valley and its tributaries. 136 records from Planktic foraminifera abundance of Hole 94-610. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 62319 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 25 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 23 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 13 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 6 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 111 records from Morphological phylogenetic analyses and taxonomic revision of the Panorpa davidi group (Mecoptera: Panorpidae). 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 2 records from Distoseptispora bambusae sp. nov. (Distoseptisporaceae) on bamboo from China and Thailand. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 33 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 3 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 124 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 588 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 118 records from Collection des mammifères d'Auvergne. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 150 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 2 records from Les Bathypalaemonellidae de Saint-Laurent, 1985 (Crustacea, Decapoda, Caridea) avec description d’une espèce nouvelle et définition d’un genre nouveau. 3 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 1 records from Ostracods from the ‘ Raibl Beds’ (Carnian, Late Triassic) of Belca section in Karavanke Mountains, northwestern Slovenia. 297 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 448 records from (Table 4) Distribution of the large, many-chambered Globigerinelloides species in the Cismon core. 98 records from Range table from benthic foraminifers in ODP Hole 146-889B. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 8 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 10 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 7 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 6 records from Ollieopteryx, a new genus of caddisflies from Madagascar (Trichoptera Dipseudopsidae). 17 records from Analyses of the recent components of sediment core PS1219-1. 67 records from Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species. 2 records from Transfer of Homalonychus raghavai Patel & Reddy, 1991 to Storenomorpha Simon 1884 (Araneae: Zodariidae). 2 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 59 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 1 records from COI mtDNA barcoding and morphology for species delimitation in the spider genus Ixchela Huber (Araneae: Pholcidae), with the description of two new species from Mexico. 2015 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 1 records from Lisubatrus dongzhiweii gen. et sp. nov. from the Gaoligong Mountains, China (Coleoptera: Staphylinidae: Pselaphinae). 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 3 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 289 records from bmhs_butterfly_collection. 1666 records from Distribution of major planktic foraminifer at Site 177-1090. 102 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 557 records from Planktic foraminifera counts of sediment core V04-8. 8 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 7 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 6 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 3402 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1 records from Discovery of termitophilous tenebrionid beetles in China (Coleoptera: Tenebrionidae). 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 875 records from Pollen profile V and Ausfluss at Krumbach, Germany. 606 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 4 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 188453 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 30 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 888 records from (UTC) University of Tennessee Mammals Collection. 19734 records from Birds Specimens. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 53 records from Planktic foraminifera abundance of Hole 23-227. 91 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 20879 records from DMNS Mammal Collection (Arctos). 35 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 216 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 1796 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 2 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 776 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 82 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 767 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 262 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 20 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 7 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1184 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 371 records from Nannofossil abundance of Hole 15-154A. 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 944 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 201 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 5 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 9 records from First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species. 53 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 138 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 7 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 1 records from The " colchicus " group of Pterostichus (Coleoptera, Carabidae). 11 records from Benthic macrofauna abundance of sediment core 12930-073. 8 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 336 records from Stable isotope data and sedimentology of core SO42-74KL. 62 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 2 records from A new species of the genus Tagasta Bolivar, 1905 (Orthoptera: Pyrgomorphidae) from India. 2 records from New biogeographical makeup for colonisation of the Baja California Peninsulaı with the description of a new Onthophagus (Coleoptera: Scarabaeidae: Scarabaeinae). 187 records from Occurrence database of native plants and animals of south-central Chile. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 828 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 4 records from Cryptic diversity across the Trans-Mexican Volcanic Belt of Mexico in the montane bunchgrass lizard Sceloporus subniger (Squamata: Phrynosomatidae). 1 records from Nothobranchius nikiforovi, a new species of seasonal killifish from the lower Matandu drainage in south-eastern coastal Tanzania (Cyprinodontiformes Nothobranchiidae). 11030 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 1 records from Archaeomalthus - (Coleoptera, Archostemata) a ‘ ghost adult ’ of Micromalthidae from Upper Permian deposits of Siberia?. 1 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 817 records from Zambian Bat Collections Worldwide. 8 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 466 records from PSU-Seagrass Collection. 26 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 532 records from Entomological collection of the National Museum. 30914 records from Vascular plants of south-central China. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 4 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 16 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 152 records from Nannofossil abundance of Hole 4-29. 33 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 808 records from Helmintos parásitos de peces del sureste de México. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 396 records from Radiolaria assemblage in sediment core GIK23259-2. 260 records from Range table from benthic foraminifers in ODP Hole 159-959A. 2 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 8 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 26 records from Carpoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 4 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 268 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 160 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 13 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 636 records from (App 10) Relative contents of indicator species of planktonic foraminifera in sediments from Core S-17666. 8 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 145 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 3 records from Three new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Taiwan. 90 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 288 records from Colección Herpetológica de la Patagonia. 6 records from Ypsolopha chicoi sp. n., the second representative of the widespread micromoth genus Ypsolopha Latreille (Lepidoptera, Ypsolophidae) from the Andes of northern Chile. 7 records from Description of Idaea josephinae sp. n. from the Iberian Peninsula (Lepidoptera Geometridae). 1 records from Dinoflagellate abundance of Hole 85-572C. 23 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 1 records from Earthworm species in various land use systems in the Campos Gerais region of Lapa, Paraná, Brazil. 13 records from Redescriptions of ten chigger mite species (Acariformes: Trombiculidae) from Vietnam. 19 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 1 records from Biodiversity of anuran endoparasites from a transitional area between the Atlantic Forest and Cerrado biomes in Brazil: new records and remarks. 3360 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 27274 records from Lepidoptera specimen database of Japan. 1 records from A review of fossil Bursidae and their use for phylogeny calibration. 38 records from Smear slide analysis on sediment core GeoB4214-1. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 166 records from Culture Collection of Algae. 273 records from Planktic foraminifera abundance of Hole 68-503B. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 33 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 1 records from Mumetopia interfeles sp. nov., a new species of Anthomyzidae (Diptera) occurring en masse in an urban grassy habitat in Chile: its taxonomy, phylogeny and biology. 44173 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 1 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 1 records from Description of a new genus and two new species of Forsteriini Tippmann, 1960 from Peru (Coleoptera, Cerambycidae, Lamiinae). 4 records from On the identity of some taxa of Pertusaria (lichens) described by C. F. E. Erichsen. 67 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 11880 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 61 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 1 records from Glossostyles perspicua gen. et sp. nov. and other fungivorous Cecidomyiidae (Diptera) new to the Czech and Slovak Republics. 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 22 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1011 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 277 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 1 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 2 records from Hypsipyrgias joseliae, a new species of lace bugs (Heteroptera: Tingidae: Tinginae) from New Guinea with a key to species of the genus Hypsipyrgias, and comments on three allied genera Hypsipyrgias Kirkaldy, 1908, Diplocysta Horváth, 1925, and Hypsotingis Drake, 1960. 79 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 63 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 2 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 5688 records from LISU Herbario Angola. 4687 records from nhmc_ob_2019. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2472 records from CNAC/Coleccion Nacional de Acaros. 187 records from Nannofossil abundance of Hole 4-31. 628 records from hauterivian_echinoids_of_the_paris_basin. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 159 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 2 records from Two new species of the genus Geckobia Mégnin, 1878 (Acariformes, Prostigmata, Pterygosomatidae) from Peru. 2 records from Notes on the taxonomy of some “ Astaena ” species described by Burmeister (Coleoptera: Scarabaeidae: Melolonthinae). 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 197 records from TransForest - vegetation, lichen and fungi data 2016. 5 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 4 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 234 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 1272 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 816 records from Línea base general de peces para el valle medio del Magdalena - VMM. 81 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 1 records from Mabuia wirzi Roux, 1925 (Squamata: Scincidae), an overlooked synonym of Dasia olivacea Gray, 1839, with notes on the synonymy of Dasia olivacea. 27 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 3 records from A new species and new record of the leafhopper genus Balclutha (Hemiptera: Cicadellidae: Deltocephalinae) from China with key to species. 127 records from Planktic foraminifera abundance of Hole 37-332. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 8 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 74 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 46 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 2 records from Two new species of nematode (Oxyurida, Hystrignathidae) parasites of Passalus interstitialis Escholtz, 1829 (Coleoptera, Passalidae) from Cuba and a new locality for Longior similis Morffe, Garcia & Ventosa, 2009. 70 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 2 records from Primulina jiangyongensis (Gesneriaceae), a new species from Southern Hunan, China. 98 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 10 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 128 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 19 records from New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 154 records from Viabilidad de semillas dispersadas por fauna en la microcuenca Teusacá, Bogotá D.C.. 9227 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 5 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 395 records from Nannofossil abundance of Hole 37-334. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 2 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 34 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 1293 records from Flora genérica de las gramíneas del estado de Tlaxcala. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 153 records from Nannofossil abundance of Hole 84-570. 75 records from Colección Palinológica del Herbario LIL (PAL-TUC-FML-Tucumán). 307 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 2 records from A new species and southernmost record of Cestrus Townes (Hymenoptera Ichneumonidae, Cryptinae). 23 records from Collembola Poduromorpha from two littoral areas of northern Rio de Janeiro Brazil. 3 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 1 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 15649 records from Natural History Museum Maastricht (NL) - Herbarium. 1 records from Naviauxella horii, a new tiger beetle species from Myanmar (Coleoptera: Cicindelidae). 128 records from Foraminifera abundance of sediment core MD81-LC07. 668 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 9331 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 169 records from Gerromorpha (Hemiptera: Heteroptera) from the Metropolitan Region of Santarém, Brazil, including three new species of Microvelia Westwood, 1834 (Veliidae: Microveliinae). 23 records from Two New Species Of Dictyogenus Klapálek, 1904 (Plecoptera: Perlodidae) From The Jura Mountains Of France And Switzerland, And From The French Vercors And Chartreuse Massifs. 5 records from New look on the geographical variation in Rhinolophus clivosus with description of a new horseshoe bat species from Cyrenaica, Libya. 4 records from Four new species of Xiphocentron Brauer, 1870 (Trichoptera: Xiphocentronidae) from the Atlantic Forest, southeastern Brazil. 8 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 17114 records from Collection of Coleoptera. 3 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 59 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 4 records from Redescription of Stilobezzia (Stilobezzia) albicoxa Lane & Forattini, 1956 with new synonymy (Diptera: Ceratopogonidae). 1 records from Gastrodia qingyunshanensis (Orchidaceae: Epidendroideae) - a new holomycotrophic orchid from Guangdong, China. 62 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 8957 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 5 records from The InBIO Barcoding Initiative Database: DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae). 21 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 88 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 6 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 2 records from A small, new gerbil-mouse Eligmodontia (Rodentia: Cricetidae) from dunes at the coasts and deserts of north-central Chile: molecular, chromosomic, and morphological analyses. 5412 records from Soil invertebrates occurrences in European North-East of Russia. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 322465 records from Queensland Museum provider for OZCAM. 52 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 6 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 746 records from IPAE egg clutches collection (Aves). 7 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 51 records from Coccoliths in sediment core GIK23065-3. 30 records from New genera for species of Jassa Leach (Crustacea: Amphipoda) and their relationship to a revised Ischyrocerini. 260 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2). 475 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 37 records from FBIP: scallop population genetics. 2474 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 27 records from Two new Hottentotta species from Iran, with a review of Hottentotta saulcyi (Scorpiones: Buthidae). 22 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 378 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 38 records from The genus Synergus Hartig (Hymenoptera: Cynipidae: Synergini) in the New World: a complete taxonomic revision with a key to species. 167 records from Read between the lineata: A revision of the tattooed wasps, Zagrammosoma Ashmead (Hymenoptera: Eulophidae), with descriptions of eleven new species. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 216 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 5 records from Society Islands beach bum black flies (Diptera: Simuliidae). 499 records from Nannofossil abundance of Hole 75-532. 2728 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 352 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 1 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 1 records from Annotated catalogue of the click-beetle tribe Senodoniini (Coleoptera: Elateridae: Dendrometrinae). 5 records from Biodiversity of spider mites (Acari: Tetranychidae) in Serbia: a review, new records and key to all known species. 16 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 6767 records from Hormigas del Museo de Entomología de la Universidad del Valle. 313 records from UWIZM Snakes. 20 records from Type material of land snails (Mollusca: Gastropoda) described from New Zealand by taxonomists in Europe and North America between 1830 and 1934, and the history of research on the New Zealand land snail fauna from 1824 to 1917. 203 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 8909 records from Actualización del conocimiento de la diversidad de especies de invertebrados marinos bentónicos de aguas someras (<50m) del Sur del Golfo de México. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 95 records from Nannofossil abundance of Hole 85-573. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 1 records from A new species of Lepidophyma (Squamata: Xantusiidae) from San Luis Potosí México, with notes on its physiological ecology. 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 665 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 53 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 44 records from Relative abundance of live benthic foraminifera of sediment core M5/2_98MC. 37 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 3438 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 6791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 54803 records from FUEL - Herbário da Universidade Estadual de Londrina. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 12 records from Atlantic Forestry Centre Insect Reference Collection. 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 46667 records from Dataflos. 113 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 3054 records from Dung Beetle Ecosystem Engineers. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 52 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 794 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 3 records from Description of a new Patagonian species of Urophonius Pocock (Scorpiones, Bothriuridae), from Meseta de Somuncurá, Argentina. 4 records from Kenai National Wildlife Refuge, Alaska (KNWR) Fish observations (Arctos). 9 records from Benthic macrofauna abundance of sediment core 12930-048. 1215 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 2979 records from Coleção de Ictiologia ABAM do Campus Sinop da UFMT. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 1 records from Ditiola haasii (Basidiomycota, Dacrymycetaceae) - taxonomy and ecology of a rare species from Central Europe. 12 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 9 records from New species of the genus Cotycicuiara Galileo and Martins, 2008 (Cerambycidae, Lamiinae, Desmiphorini). 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 34 records from Planktic foraminifera abundance of Hole 63-472. 11 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 2327 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 298 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 4 records from Descriptions of two new Vietomartyria species (Lepidoptera, Micropterigidae) from China. 15161 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 147 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 6 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 206 records from Planktic foraminifera abundance of Hole 15-149. 143 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 7 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 1 records from A Revision of Philander (Marsupialia: Didelphidae), Part 2: Phylogenetic Relationships and Morphological Diagnosis of P. nigratus Thomas, 1923. 32 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 17 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 917 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 4845 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 67 records from Relative abundance of ostracods in sediment core Sv09. 102 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 23 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 9 records from A New Species Of Perlesta (Plecoptera: Perlidae) From North Carolina With Additional Records For North Carolina And Virginia. 2 records from New records for chewing lice of the genus Dennyus Neumann, 1906 (Phthiraptera: Amblycera) on two swifts from Saudi Arabia. 1 records from The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae). 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 94 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 28 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 33372 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 331 records from Range table from planktonic foraminifers in ODP Hole 182-1129C. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 91851 records from NE AVH data. 24 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 1853 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla (Plantas). 4 records from First record and new species of the genus Calambus Thomson (Coleoptera Elateridae, Dendrometrinae) from Taiwan. 1 records from A new species of planthopper in the genus Haplaxius (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) on palms in Costa Rica and a new country record for Haplaxius skarphion. 38452 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 6 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 3 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 7798 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 3444 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 23 records from Benthic foraminifera abundance of Hole 42-379A. 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 42 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 4 records from NZCS Paloemeu River - Grensgebergte Mountains Expedition Conservation International RAP 2012. 21 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 2494 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 49 records from Coccoliths in sediment core PS1535-8. 12 records from Newly recorded leafhoppers of the subfamily Cicadellinae (Hemiptera: Cicadellidae) with description of a new species from Pakistan. 1 records from First record of Coillina baka Ying & Peng, 1998 (Araneae: Gnaphosidae) from Myanmar, with a description of the previously unknown female. 8 records from Report on a collection of dragonflies (Odonata) from the Andaman Islands.. 10 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 44 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 15874 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 2 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 2 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 1 records from World catalogue of the Hydrophiloidea (Coleoptera): additions and corrections II (2006 - 2010). 3 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 1 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 6 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 28 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 10953 records from Brown University Herbarium. 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 1 records from A new species of Enosis Mabille, 1889 (Lepidoptera, Hesperiidae, Hesperiinae) from southern Brazil and notes on Enosis angularis (Möschler, 1877). 17 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 40 records from Revision of Chinese crickets of the tribe Modicogryllini Otte & Alexander, 1983 with notes on relevant taxa (Orthoptera: Gryllidae; Gryllinae). 1482 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 2765 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 28 records from Revision of the Metallactus generosus species-group with a preliminary evaluation of the effectiveness of the endophallus morphology in distinguishing critical sibling species (Coleoptera: Chrysomelidae: Cryptocephalinae). 2 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 736 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 1 records from Redescription of larva of the South African endemic dobsonfly genus Chloroniella Esben-Petersen, 1924 (Megaloptera, Corydalidae), with a proposed terminology for Corydalidae larval sclerites. 17 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 2 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 23 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 78 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 4078 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 1 records from A reappraisal of the California Roach / Hitch (Cypriniformes, Cyprinidae, Hesperoleucus / Lavinia) species complex. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 15 records from Benthic macrofauna abundance of sediment core 13201-002. 3 records from Studies on Neotropical crickets: New species and notes on the classification of Field Crickets genera Anurogryllus and Gryllus (Orthoptera: Gryllidae: Gryllinae). 12 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 1 records from A new species of Pestalotiopsis from leaf spots of Licuala grandis from Hainan, China. 453 records from Pollen profile from Muscotah Marsh B. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 614 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 52 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 51 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 1 records from Studies on Ramulus ussurianus (Bey-Bienko, 1960) (Phasmida: Phasmatidae). 9 records from Planktic foraminifera abundance of Hole 14-144. 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 530 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 1468 records from Colección Regional de Equinodermos de la Peninsula de Yucatan. 6 records from Description of Harpactea popovi sp. n. from Bulgaria with further taxonomic notes on related species (Araneae, Dysderidae). 8 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 8435 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 121 records from Range table from ostracoda in ODP Hole 143-866B. 5 records from Anderemaeus (Acari, Oribatida) - overview, three new species from South America and reassessment of Anderemaeidae supported by ontogeny. 5929 records from Colección Limnológica Universidad de Antioquia. 3 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 648 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 239 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 181184 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 232 records from Conservación y monitoreo de anfibios en riesgo de extinción en Chiapas. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 49 records from A new species of Aframomum (Zingiberaceae) from Central Africa. 2177 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 96 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 4 records from First record of the myrmicine ant genus Syllophopsis Santschi, 1915 (Hymenoptera Formicidae) from India with description of a new species. 11 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1 records from A new species of Platyauchenia Stürm, 1843 (Coleoptera: Chrysomelidae: Cassidinae) from Brazil. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 19 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 1597 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 10 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 199 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 5 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 43 records from Six new species of Anthuridae (Peracarida: Isopoda) from the southern Mexican Pacific. 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 1 records from REVISÃO DO GÊNERO “ LEPTOCYSTA ” STAL (Hemiptera, Tingidae). 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 164 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 899 records from Stable isotopes and content of foraminifera at Hole 130-805C. 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 1179 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 37 records from Mammals collected and illustrated by the Baudin Expedition to Australia and Timor (1800 - 1804): A review of the current taxonomy of specimens in the Muséum national d’Histoire naturelle de Paris and the illustrations in the Muséum d’Histoire naturelle du Havre. 10 records from Ostracoda abundance of Hole 32-306. 244 records from Nannofossil abundance of Hole 29-281. 3 records from New species of karst-dwelling Pselaphinae from southwestern China (Coleoptera: Staphylinidae). 7584 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 2 records from Review of the Australian Signal Flies of the Genus Microepicausta (Diptera: Platystomatidae). 1 records from Redescription of Neponymphes godoii Zamboni, 2001 from the Lower Cretaceous of Brazil, based on the adult and nymphal stages (Hemiptera: Nepomorpha: Belostomatidae). 194 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 11 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 11877 records from Formidabel; Belgian Ants Database. 92 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 46 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 196 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2316 records from VKM Microbial Cultures from Former USSR. 7 records from Three new species of the subgenus Jaynesia Allen, 1969 of the genus Tiphia Fabricius, 1775 (Hymenoptera: Tiphiidae: Tiphiinae) from China, with a key to all known species. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 4 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 155236 records from CAS Invertebrate Zoology (IZ). 18 records from Ophioderma hendleri sp. nov. (Echinodermata: Ophiuroidea: Ophiodermatidae) and its congeners from the Eastern Pacific. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 29 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 79 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 2352 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 750 records from 2013_nsmk_smpl_in. 830 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 102 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 53460 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 15 records from A new leafhopper genus Discolopeus and nine new species (Hemiptera, Cicadellidae, Deltocephalinae) associated with shrubs, trees and poisonous plants in South Africa. 58 records from Сypripedium guttatum Sw. in the Komi republic. 1 records from Skull anatomy and phylogenetic assessment of a large specimen of Ecteniniidae (Eucynodontia: Probainognathia) from the Upper Triassic of southern Brazil. 3676 records from NSW South Coast & ACT plants. 2 records from The first species of Cotithene Voss (Coleoptera: Curculionidae: Curculioninae) from Amazonian Brazil, with notes on its role as a pollinator of Evodianthus funifer (Poit.) Lindm. (Cyclanthaceae). 1 records from First report of Cleruchoides Lin & Huber (Hymenoptera: Mymaridae) from the Oriental region with description of a new species from India. 2 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 54 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 31 records from Planktic foraminifera counts of sediment core V19-21. 69 records from artsprosjektet_48-13_monomyx. 154 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 3 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 5154 records from Colección Ornitológica de la Universidad del Valle. 287 records from On the Italian species of Drusilla L, 1819, with a note on D. taygetana A (Coleoptera: Staphylinidae, Aleocharinae). 16 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 19 records from Revision of the South American species of Austrothaumalea Tonnoir (Diptera Thaumaleidae). 2 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 102 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1313 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 224 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 2 records from Nomenclatural notes on Ferula tunshanica (= F. licentiana var. tunshanica) (Apiaceae). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 54 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 19 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 2 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 136 records from (Table 9) Relative abundance of benthic foraminifera in ODP Hole 112-685A. 7 records from Deep-sea ascidians from Papua New Guinea. 56 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3 records from Indian Hecalina (Hemiptera: Cicadellidae: Deltocephalinae: Hecalini) with description of three new species. 101967 records from NatureServe Network Species Occurrence Data. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 4 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 839 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 23 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1748 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 39 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 1 records from On the morphology of the astragalus and calcaneus of the amphicyonids (Carnivora, Mammalia) from the Paleogene of Europe: implications for the ecology of the European bear-dogs. 2 records from A new species of Scinax Wagler (Hylidae: Scinaxini) from the tropical forests of Northeastern Brazil. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 25 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 7 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 114 records from Three new species of Oxypoda from Spain, Armenia, and Ukraine with notes on the fauna of Armenia (Coleoptera: Staphylinidae: Aleocharinae). 3 records from A New Species of Cryptopontius (Crustacea: Copepoda: Siphonostomatoida) from Easter Island. 42 records from The Calliphoridae (Diptera) of Armenia. 460 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 2 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 238 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P9. 7 records from Content of G. menardii in sediment core V25-70. 2850 records from Pollichia Pilzherbar. 3 records from A Revision of Extant Greater Antillean Bats of the Genus Natalus. 5 records from Revision of the types of species of Alloxysta described by Cameron and Fergusson (Hymenoptera: Figitidae: Charipinae) and deposited in the Natural History Museum (London), including a key to the fauna of Great Britain. 452 records from Neogene palynomorpha from site 93-603, part 2. 18 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 3588 records from Fish Collection of National Museum, Philippines. 38 records from Range table from planktonic foraminifers in ODP Hole 167-1010E. 2 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 800 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 28 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 8685 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 81 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 692 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 2952 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 53225 records from MCP - Coleção de Abelhas. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 4 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 2 records from Charinus rocamadre (Amblypygi, Charinidae): description of the female, ultrastructure of the male and female gonopods, and mitochondrial DNA sequences. 364 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 1867 records from SCFS - Sagehen Herbarium. 35 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 1 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 281 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 5 records from Aglaotilla, a new genus of Australian Mutillidae (Hymenoptera) with metallic coloration. 36407 records from R. L. McGregor Herbarium Lichen Collection. 278 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 14 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 11046 records from Oregon Bee Atlas Survey Data: 2018. 1155 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 10280 records from UAM Fish Collection (Arctos). 3 records from Rideriana amazonica gen. nov. and sp. nov. of Pentatomini (Heteroptera, Pentatomidae). 8 records from University of Sargodha Herbarium. 8808 records from Survey of bumblebees in central Alberta - 2018. 70 records from Isotope tracer experiment: meiofauna counts. 3252 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 6 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 23 records from Nannofossil abundance of Hole 94-611E. 122 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 9292 record
Keywords: GBIF; biodiversity; species occurrences